Investigating the Effect of Glucose 6-Phosphate Dehydrogenase Deficiency (G6PDd) and Haemoglobin Variants on Malaria in Port Harcourt, Rivers State, Nigeria - Akwuebu, Susanna O.; Eze, Evelyn M.; Jeremiah, Zacchaeus A. (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Malaria disease burden is thought to follow the same geographical pattern as G6PD deficiency and sickle cell haemoglobin (HbSS) due to a protective advantage against malaria parasites. Malaria during pregnancy is a major public health concern that kills both mothers and infants and mortality in malaria-endemic countries. The purpose of this study was to investigate the interactions between G6PD and haemoglobin variants in pregnant women with subclinical malaria. Five millilitres (5ml) of venous blood was collected aseptically and carefully mixed into a 1 percent diamine tetraacetic acid bottle for analysis. G6PD activity was quantified using a 3000 BSA spectrophotometer and the Randox G6PD kit. The density of malaria parasites was measured microscopically using thick and thin Giemsa stained blood smears.Haemoglobin variants were identified using cellulose acetate membrane electrophoresis with Tris-EDTA-borate buffer (pH 8.9).All results were analysed using p values as a measure of significance, with (p>0.05) considered insignificant and p<0.05 considered significant. The study drew a total of eight hundred and twenty-eight (828) participants.Of these, five hundred and seven 507 (61.2%) were infected with malaria parasite and three hundred and twenty-one (321) (38.8%) served as controls (uninfected subjects). In malaria parasite infection, the HbAA genotype dominated with 379 (74.8%), followed by HbAS 126 (24.9%), and HbSS 2 (0.4 percent ). The average age of the participants in the study was 29.5+5.31 years. In addition, out of the eight hundred and twenty-eight participants, 517 (62.4 percent) were G6PD deficient. HbSS had a substantially higher mean G6PD level of 12.20+0.30u/gHb than HbAS, which was 6.28+0.16u/gHb, and HbAA, 6.60+0.07u/gHb. As a result, co-inheritance of G6PD and HbS offers no benefit over single inheritance of the HbS variant.